A thermodynamic review of solar air heaters. (March 2015) - Saxena, Abhishek; Varun,; El-Sebaii, A.A.
Abstract: Solar air heaters (SAHs) form the foremost component of solar energy utilization system. These air heaters absorb the irradiance and convert it into thermal energy at the absorbing surface and then transfer this energy to a fluid flowing through the collector. SAHs are inexpensive and most used collection devices because of their inherent simplicity. SAHs are found in several solar energy applications, especially for space heating, timber seasoning and agriculture drying. It has been observed by studying the previous literature that all the elements of a solar air heater such as; an absorber tray, the ducts, glazing, insulation, extended surfaces, as well as the tilt angle, have a significant effect on the thermal performance of the system. This review article focus on the developments that has followed round the globe in various aspects of solar air heating systems since 1877 up to now, with a glimpse of some novel patents of SAHs. The various methods that are used to improve the thermal performance of SAHs such as; optimizing the dimensions of the air heater construction elements, use of extended surfaces with different shapes and dimensions, use of sensible or latent storage media, use of concentrators to augment the available solar radiation, integrating photovoltaic elements with the heaters, etc, are also reported. Besides this, some benefits by using the SAHs has been discussed.